STUDENTS' RESPONSES TOWARDS THE IMPLEMENTATION OF GAME BASED LEARNING WITH DOMINO CARDS ON THE BLOOD CIRCULATORY SYSTEM MATERIAL: RESPON SISWA TERHADAP IMPLEMENTASI GAME BASED LEARNING DENGAN MEDIA KARTU DOMINO PADA MATERI SISTEM PEREDARAN DARAH - Aida Hanun Shofiyah; An Nuril Maulida Fauziah (PENSA E-JURNAL: PENDIDIKAN SAINS, 2025)
This study aims to determine students' responses to the implementation of game-based learning (GBL) using domino card media on the topic of the circulatory system. The study uses qualitative research using literature review method. The research instrument used student response questionnaire distributed to 24 junior high school students. Data collection was carried out through the distribution of questionnaires regarding students’ responses to the implementation of GBL with domino card media on the circulatory system topic. The collected data will be analyzed by calculating the percentage of each statement in the student response questionnaire to determine the proportion of positive and negative responses. The results of the study show that the number of positive responses was higher than the negative responses regarding the implementation of GBL using domino card media on the circulatory system topic.